2020
DOI: 10.1080/09537287.2020.1818326
|View full text |Cite
|
Sign up to set email alerts
|

How purchasing departments facilitate organizational ambidexterity

Abstract: Companies must pursue both exploration and exploitation of supplier's knowledge in increasingly competitive and complex production environments. This has been referred to as pursuing an ambidextrous supply strategy, extending the mobilisation of resources in pursuit of both aims beyond the borders of the lead manufacturer and into supplier organizations as well. Purchasing and supply management plays an increasingly central role in mobilizing and involving the suppliers in the pursuit of this agenda. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 71 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Recent studies find a new role for purchasing connecting R&D and purchasing becoming known as "innovation purchasing" (Servajean-Hilst and Calvi, 2018). This new duality has given rise to an emerging ambidexterity perspective that emphasises the opposite and potentially conflicting role of purchasing in having to balance the traditional cost-saving (exploitation) and new innovation-focused (exploration) roles (Andersen et al, 2021;Constant et al, 2020;Gualandris et al, 2018).…”
Section: Type Of Innovation: Increasing Focus On Technological Uncert...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies find a new role for purchasing connecting R&D and purchasing becoming known as "innovation purchasing" (Servajean-Hilst and Calvi, 2018). This new duality has given rise to an emerging ambidexterity perspective that emphasises the opposite and potentially conflicting role of purchasing in having to balance the traditional cost-saving (exploitation) and new innovation-focused (exploration) roles (Andersen et al, 2021;Constant et al, 2020;Gualandris et al, 2018).…”
Section: Type Of Innovation: Increasing Focus On Technological Uncert...mentioning
confidence: 99%
“…Adopting theoretical perspectives from other fields, such as ambidexterity or absorptive capacity, can also open up new lines of inquiry and provide new evidence for the existence of this research field. For example, we can observe how the dual -and potentially conflictingchallenges for purchasing to contribute effectively to innovation exploitation and exploration (Schiele, 2010) can be usefully researched through an ambidexterity lens; recent publications have explored this theme (Andersen et al, 2021;Constant et al, 2020;Gualandris et al, 2018).…”
Section: Consider New Theoriesmentioning
confidence: 99%
“…Our study contributes to the SSCM and agility literature by focusing on the sustainability practices-firm performance link and showing that SSCM practices can be appropriate strategic choices to improve agility performance. Second, a firm's ambidextrous orientation, which provides different organizational responses to conflicting environmental demands (Andersen et al, 2021), is investigated as a moderator influencing sustainable sourcing's effect on agility performance. Ambidexterity theory has been applied in several areas, like ambidextrous governance (Lin and Ho, 2021), ambidextrous organizational design (Jansen et al, 2012), and supply chain ambidexterity (Aslam et al, 2020).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Among the increasing literature on agility, some influentially environmental factors at different levels are identified that might affect the relationship between sustainable sourcing and agility (e.g. Andersen et al, 2021; Aslam et al, 2018; Inman and Green, 2021; Jajja et al, 2018; Shekarian et al, 2020; Tuan, 2016). According to ERBV, we argue that the impact of sustainable sourcing on agility is mainly due to resource benefits derived from sustainable sourcing.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) advance purchasing ambidexterity and examine its multiple performance outcomes. Furthermore, Andersen et al. (2020) explore how purchasing departments contribute to ambidexterity by involving suppliers and acquiring their knowledge.…”
Section: Theoretical Backgroundmentioning
confidence: 99%